Ultrasonic characterization of the fat source and composition of formulated dry-cured meat products - Jimenez, Edith Corona (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2014)
The aim of this work was to test the feasibility of using ultrasonic measurements to estimate the fat content and identify the fat sources used in formulated dry-cured pork meat products. For that purpose, dry-cured sausages were prepared using different fat sources (two Iberian pork backfats, Iberian lard, and sunflower oil) and contents (fat content from 3% to 17% wet basis) and characterized by measuring the ultrasonic velocity (at 2 degrees C, 6 degrees C, 10 degrees C, 15 degrees C, 20 degrees C, and 25 degrees C), fatty acid profile, thermal behavior, and composition. The fatty acid composition affected the melting behavior of the sausages, which also involved different ultrasonic velocities, depending on the fat source used for the sausage formulation. Significant (p < 0.05) linear relationships were established between the ultrasonic velocity and the percentage of melted fat, by means of which the sausage batches were differentiated according to the fat source used. The ultrasonic velocity temperature dependence allowed the determination of the fat content (explained variance 96.1%) by measuring the ultrasonic velocity in the dry-cured sausages at 2 degrees C and 25 degrees C and using a semi-empirical equation. Therefore, the ultrasonic measurements could be considered as a reliable tool for the characterization and differentiation of formulated dry-cured meat products with different fat sources and contents